2017
DOI: 10.1080/00222895.2017.1306480
|View full text |Cite
|
Sign up to set email alerts
|

Can Video Self-Modeling Improve Affected Limb Reach and Grasp Ability in Stroke Patients?

Abstract: The authors examined whether feedforward video self-modeling (FF VSM) would improve control over the affected limb, movement self-confidence, movement self-consciousness, and well-being in 18 stroke survivors. Participants completed a cup transport task and 2 questionnaires related to psychological processes pre- and postintervention. Pretest video footage of the unaffected limb performing the task was edited to create a best-of or mirror-reversed training DVD, creating the illusion that patients were performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Although our PSR VSM intervention yielded mixed results, we believe it has potential value in clinical settings based on evidence for its effectiveness with special populations (e.g., Dowrick & Raeburn, 1995;Steel et al, 2018) and its theoretical utility for facilitating skill acquisition when specific strategies and individual needs can be matched. For example, following the discovery of a mirror neuron system in the brains of monkeys, several investigators (Di Pellegrino et al, 1992;Rizzolatti et al, 1996) showed that action observation is associated with increased cortical excitability in the primary motor cortex and in brain areas involved in movement planning, anticipation and execution (e.g., Gangitano et al, 2001;Gonzalez-Rosa et al, 2015;Holmes & Calmels, 2008;Loporto et al, 2013;Wrightson et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although our PSR VSM intervention yielded mixed results, we believe it has potential value in clinical settings based on evidence for its effectiveness with special populations (e.g., Dowrick & Raeburn, 1995;Steel et al, 2018) and its theoretical utility for facilitating skill acquisition when specific strategies and individual needs can be matched. For example, following the discovery of a mirror neuron system in the brains of monkeys, several investigators (Di Pellegrino et al, 1992;Rizzolatti et al, 1996) showed that action observation is associated with increased cortical excitability in the primary motor cortex and in brain areas involved in movement planning, anticipation and execution (e.g., Gangitano et al, 2001;Gonzalez-Rosa et al, 2015;Holmes & Calmels, 2008;Loporto et al, 2013;Wrightson et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…In the FF technique, the video footage is edited to show the person performing the skill at a level not yet achieved (Anderson et al, 2014). VSM has been applied extensively in domains such as education (Hitchcock et al, 2003), with growing interest in its use, amongst other observational techniques, for movement and rehabilitation domains (Coulson et al, 2006;Holmes, & Calmels, 2008;Rymal & Ste-Marie, 2019;Steel et al, 2018;Wrightson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several video self-modeling studies have directly focused on aspects of physical health (Coulson et al, 2006;Dowrick & Dove, 1980;Foltz, 2014;Hagin et al, 2015;Steel et al, 2017). These studies emphasized athletic performance (Foltz, 2014;Hagin et al, 2015) and physical recovery to gain nonimpaired physical functioning (Coulson et al, 2006;Dowrick & Dove, 1980;Steel et al, 2017).…”
Section: Effects On the Bodymentioning
confidence: 99%
“…[14]) und einem effektiveren Lernen. Steel und Kollegen [17] zeigten Patienten mit Schlaganfall ein bearbeitetes Video zum Hantieren mit Bechern und stellten ausschließlich die besten Versuche mit dem weniger betroffenen Arm der Patienten spiegelverkehrt dar.…”
Section: Erhöhte Leistungserwartungunclassified